The Examination of Demographics Influences on the Digital Parenting Awareness of Parents With 3-6 Years Old Children - Kulaksız, Taibe; TORAN, MEHMET (Van Yüzüncü Yıl Üniversitesi, Eğitim Fakültesi, 2023)
This study aims to reveal the differences between digital parenting awareness by gender of the parent, age of the parent, perceived socioeconomic status of parent, daily internet usage duration of the parent, educational level of the parent, age of the child, number of children, and using a control app. Utilizing a cross-sectional survey method, the participants of the study consist of 308 parents with children ages 3 to 6. The Demographic Information Form and Digital Parenting Awareness Scale were administered and analyzed based on quantitative parametric analysis methods. Results showed that some demographics vary between mothers’ and fathers’ digital parenting awareness. Mothers show higher digital parenting awareness. Older parents are inclined to be digitally negligent of their children. Parents’ socioeconomic and educational levels almost do not influence digital parenting awareness. Parents do not act differently in digital environments regarding their pre-school age children. One-child families protect their kids from digital risks more than three-child families. It is important to emphasize that parents using the internet daily for more than four hours tend to have less awareness. Fathers/mothers using a parental control app have higher awareness to save and monitor their children online.
Keywords: Parenting; Digital Parenting Awareness; Children; Technology